A multinational megastudy of the effects of gratitude practices on subjective well-being - Nicholas A. Coles; Annabel V. Dang; Shigehiro Oishi; Abigail Adade; Aderonke A. Akintola; Beatriz B. de Souza; Biljana Gjoneska; Christine R. Harris; Dev Kesarwani; Dinara Pisareva; Eugene Y. J. Tee; Goo Lyann; et al. (Proceedings of the National Academy of Sciences, 2026)
Scholars have observed people from a variety of cultures using a variety of gratitude-related practices to change their emotions, outlooks, and social relationships. Across 34 countries purposively sampled to cover a broad set of cross-cultural differences (total N = 10,696), we experimentally tested the effects of 6 brief gratitude interventions on subjective moods, life outlooks, and social evaluations. Compared to 3 control tasks, gratitude practices immediately produced theorized improvements in positive affect ( d = 0.37), negative affect ( d = −0.22), optimism ( d = 0.24), life satisfaction ( d = 0.12), indebtedness ( d = 0.15), and envy ( d = −0.16). Notably, these effects varied across different gratitude practices (0.00 < τ practice < 0.08) and countries (0.10 < τ country < 0.19). For instance, based on existing evidence, stakeholders can expect gratitude interventions deployed in a randomly selected country to improve positive affect—but not our other measured outcomes. To guide future inquiry into why this might be the case, we provide exploratory Bayesian estimates of the importance of 12 cross-cultural differences.